MAN 4 Aceh Besar في تدريس الاستماع بـــ Fun Easy Learn Arabic استخدام برنامج - Ulfa, Rizqia; Mahmud, Salami (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2024)
From observations conducted by the researcher at MAN 4 Aceh Besar, it was revealed that Arabic language teachers only use textbooks and PowerPoint presentations, apply selective teaching methods, and strive to teach Arabic well. However, students feel bored and uninterested in learning Arabic, especially in listening lessons, which makes it difficult for them to understand the material being taught. The researcher found that students have difficulty in remembering vocabulary, perhaps due to the lack of suitable teaching methods for teaching listening skills. Therefore, the researcher aims to develop students' abilities in learning Arabic, especially in listening lessons. Thus, the researcher wrote this thesis entitled